Mechanical Behavior and Damage Evolution for Granite Subjected to Cyclic Loading - Zhiliang Wang; Jikang Yao; Nuocheng Tian; Jingbin Zheng; Peng Gao (Advances in Materials Science and Engineering)
This paper focuses on the mechanical behavior and damage evolution of Huashan granite subjected to cyclic loading. Four levels of confining pressure (0, 15, 25, and 35 MPa) were applied during cyclic axial loading by using a Rock Test System (MTS815) along with an acoustic emission (AE) monitoring device. Experimental results indicate that the number of AE activities is higher under cyclic triaxial loading compared to that under cyclic uniaxial loading. The measured stress-strain curves of both uniaxial and triaxial tests under cyclic loading are concave-up, but the degree of concavity is mild for the latter. As the cycle number rises, elastic modulus of the granite sample under different confining pressures increases. The slope of the peak strength versus confining pressure plot for the cyclic loading is larger than that for the monotonic loading. Besides, it is found that the dissipated energy increases with the increase of cyclic stress, but it hardly increases in proportion with the confining pressure. The damage parameters defined in terms of the plastic strain can be extended for the whole cyclic loading process, and they agree well with the energy-based damage parameters.